2017
DOI: 10.3892/mco.2017.1176
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of nanoparticle albumin-bound paclitaxel, carboplatin and trastuzumab in women with human epidermal growth factor receptor 2-overexpressing breast cancer

Abstract: Abstract. Although the concurrent use of anthracycline-containing chemotherapy and taxane with trastuzumab are considered the treatment of choice for the primary systemic therapy of human epidermal growth factor receptor 2 (HER2)-overexpressing early breast cancer, non-anthracycline regimens, such as concurrent administration of docetaxel and carboplatin with trastuzumab, exhibited similar efficacies in a previous study. In addition, tri-weekly treatment with nanoparticle albumin-bound paclitaxel (nab-paclitax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…No DLT was observed during the first cycle, however, 4 patients developed grade 4 thrombocytopenia, 2 had grade 4 neutropenia and 3 exhibited a grade 4 decrease in hemoglobin levels. The study concluded that although no DLTs were observed in the first cycle of the treatment, hematological toxicity (anemia) presented difficulties with continuity [112].…”
Section: Nanoparticles For Combination Therapy In Bcmentioning
confidence: 99%
“…No DLT was observed during the first cycle, however, 4 patients developed grade 4 thrombocytopenia, 2 had grade 4 neutropenia and 3 exhibited a grade 4 decrease in hemoglobin levels. The study concluded that although no DLTs were observed in the first cycle of the treatment, hematological toxicity (anemia) presented difficulties with continuity [112].…”
Section: Nanoparticles For Combination Therapy In Bcmentioning
confidence: 99%
“…Furthermore, Abraxane® promoted higher tumor accumulation of paclitaxel (~33%), inhibited elimination (4-fold decrease) [37] , and demonstrated a superior overall response rate (34%) compared to paclitaxel (19%) in patients with advanced breast cancer [38] , [58] . Importantly, combination therapies of Abraxane® with conventional chemotherapeutic agents and targeted therapies have also demonstrated safety and superior efficacy compared to single therapies in clinical trials [52] , [53] . Lipusu® (China, 2003) was the first liposomal formulation of paclitaxel approved for the treatment of non-small lung cancer, ovarian, and breast cancer [41] , [42] , [51] , [56] .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion to different clinical trials, Abraxane showed more efficient results over solvent-based paclitaxel, and can be used with chemotherapy and other targeted therapies. [30] Passive and active targeting of nano-carriers in breast cancer treatment…”
Section: Abraxanementioning
confidence: 99%